2015
DOI: 10.1002/humu.22838
|View full text |Cite
|
Sign up to set email alerts
|

GenomeConnect: Matchmaking Between Patients, Clinical Laboratories, and Researchers to Improve Genomic Knowledge

Abstract: As the utility of genetic and genomic testing in healthcare grows, there is need for a high quality genomic knowledge base to improve the clinical interpretation of genomic variants. Active patient engagement can enhance communication between clinicians, patients and researchers, contributing to knowledge building. It also encourages data sharing by patients and increases the data available for clinicians to incorporate into individualized patient care, clinical laboratories to utilize in test interpretation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 14 publications
0
52
0
Order By: Relevance
“…In summary, this paper provides an overview of the MME, from its founding principles and goals to the steps required to launch it as a robust platform for rare disease discovery. The ensuing papers in this special issue of Human Mutation define many of the individual matchmaker services already connected [Buske, et al., a; Chatzimichali et al., ; Sobreira et al., ), or intending to connect to the federated network [Lancaster et al., 2015; Kirkpatrick et al., ; Lambertson et al., ; Mungall et al., ], as well as other core components [Buske et al., b] and concepts [Akle et al., ; Krawitz et al, ] that support genomic matchmaking. A few case examples of discoveries already made through use of matchmaking approaches are highlighted to add further support for this robust approach to rare disease gene discovery [Au et al., ; Jurgens et al., ; Loucks et al., ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, this paper provides an overview of the MME, from its founding principles and goals to the steps required to launch it as a robust platform for rare disease discovery. The ensuing papers in this special issue of Human Mutation define many of the individual matchmaker services already connected [Buske, et al., a; Chatzimichali et al., ; Sobreira et al., ), or intending to connect to the federated network [Lancaster et al., 2015; Kirkpatrick et al., ; Lambertson et al., ; Mungall et al., ], as well as other core components [Buske et al., b] and concepts [Akle et al., ; Krawitz et al, ] that support genomic matchmaking. A few case examples of discoveries already made through use of matchmaking approaches are highlighted to add further support for this robust approach to rare disease gene discovery [Au et al., ; Jurgens et al., ; Loucks et al., ].…”
Section: Discussionmentioning
confidence: 99%
“…There are already examples of patients who have played such roles in identifying causes of rare disease [Lambertson et al., ] and the MME intends to better support their efforts. Two manuscripts in this special issue describe how patients themselves have taken an interest in matchmaking and are creating their own systems both within and apart from the MME [Kirkpatrick et al., , Lambertson et al., ].…”
Section: Introductionmentioning
confidence: 99%
“…G e n o m e C o n n e c t ( w w w. genomeconnect.org), a web-based patient registry created as part of the NIH-funded Clinical Genome Resource to promote patient-centric data sharing of genotype and phenotype information, is open to anyone who has undergone genetic testing, is considering genetic testing, or is a family member (i.e. parent) of someone who has had testing, regardless of genetic testing results or diagnosis (Kirkpatrick et al, 2015). The majority of GenomeConnect participants have indicated that they or their child underwent genetic testing because they had symptoms of a genetic condition, had a family member with a genetic condition, or their doctor wished to confirm a diagnosis.…”
Section: Participantsmentioning
confidence: 99%
“…In addition to regulatory, ethical, and legal considerations, frameworks from professional bodies have been constructed to guide experienced clinicians in their interpretation and reporting of genomic information (39,40). Data-sharing efforts by researchers and providers of clinical genetic testing are increasing the body of knowledge for specific genes and variants, information that is fundamental to the process of interpreting genetic variation in an informed clinical context (41,42). …”
Section: Current Methods In Genome Sequencingmentioning
confidence: 99%